Green Product Purchase Intention - Aang Muhammad Nur Shidiq; Arry Widodo (Jurnal Sekretaris dan Administrasi Bisnis, 2018)
Green products are environmentally sound products, designed and processed in a way to reduce the effects that may pollute the environment, whether in production, distribution and consumption. This study is conducted to determine the effect of green brand knowledge mediated attitudes toward the green brand and how it affects the intention to buy green products manufactured by Twin Tulipware. The purpose of this research is to know and analyze how the green brand knowledge, how the attitude toward the green brand, how the intention to buy green products, the amount of influence knowledge and green attitude to purchase intention of green products manufactured by Twin Tulipware directly and indirectly. The researchers use three research variables categorised as the independent variables and dependent variable. The research method applied in this study is a quantitative inquiry. Sampling is done by non-probability sampling method with accidental sampling type, with 100 respondents, knowing and using Twin Tulipware product. The data are collected by using questionnaires. The results show that the direct effects of green brand knowledge on the intention to buy green products are 49.5% and indirect influence through the attitude toward the green brand is 21%. Therefore, the total effect of green brand knowledge on the intention to buy green products through the attitude of the green brand is 70.5%. Knowledge and attitude have a R2 (R Square) value of 56.6% of the intention to buy green products.